2019
DOI: 10.1016/j.bbr.2019.02.042
|View full text |Cite
|
Sign up to set email alerts
|

High-fructose diet initiated during adolescence does not affect basolateral amygdala excitability or affective-like behavior in Sprague Dawley rats

Abstract: Patients with type-2 diabetes, obesity, and metabolic syndrome have a significantly increased risk of developing depression. Dysregulated metabolism may contribute to the etiology of depression by affecting neuronal activity in key limbic areas. The basolateral amygdala (BLA) acts as a critical emotional valence detector in the brain's limbic circuit, and shows hyperactivity and abnormal glucose metabolism in depressed patients. Furthermore, administering a periadolescent high-fructose diet (HFrD; a model of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 74 publications
0
3
1
Order By: Relevance
“…However, it should be borne in mind that these findings and the behavioral anxiety tests employed reflect only a small part of the emotional state tested, and do not reflect the entire emotional prism of the animals. On the other hand, contrary to the results of our study, O'Flaherty's study showed no effects of fructose intake on affective behavior tested in the OFT, in male Sprague-Dawley rats [18]. This is perhaps due to methodological differences related to housing conditions, the type of rats, or even the test procedures used [19].…”
Section: Effects On the Anxiety-like Behavior Determined In The Oftcontrasting
confidence: 99%
“…However, it should be borne in mind that these findings and the behavioral anxiety tests employed reflect only a small part of the emotional state tested, and do not reflect the entire emotional prism of the animals. On the other hand, contrary to the results of our study, O'Flaherty's study showed no effects of fructose intake on affective behavior tested in the OFT, in male Sprague-Dawley rats [18]. This is perhaps due to methodological differences related to housing conditions, the type of rats, or even the test procedures used [19].…”
Section: Effects On the Anxiety-like Behavior Determined In The Oftcontrasting
confidence: 99%
“…Consequences of excess sugar Ample evidence directly connects obesogenic diets to depressive-and anxiety-like behaviors in rodents; however, the contribution of excess sugars typically present in such diets demands attention. While sugar consumption can alleviate stress and pain and improve negative mood and emotional states in the short-term [52], prolonged intake of high sucrose or fructose diets can induce anxiety-and depressive-like behaviors and motivational deficits [53][54][55], effects that are more pronounced during the adolescent period [55][56][57]. The presence of excess sugar in a HFD was shown to be necessary for hypothalamic inflammatory responses in mice, including the activation of microglia, the resident immune cells of the brain [58].…”
Section: Dietary Fat Overloadmentioning
confidence: 99%
“…Similarly, a high-fructose diet during adolescence elicited increased anxiety-like and depressive-like behavior in adulthood, while these responses did not occur in rats fed a high fructose diet during adulthood only [ 92 ]. Differently from these results, a study on Sprague Dawley rats revealed that high fructose diet (55% kcal from fructose) feeding from adolescence until adulthood, although disrupting animal metabolism, did not affect anxiety-like or depressive-like behavior, nor did it modify the intrinsic excitability of basolateral amygdala principal neurons [ 93 ]. These findings suggest that the effect of a fructose rich diet on affective behavior may be tightly dependent on strain and age.…”
Section: Fructose Cognitive Function Aging and Neurodegenerativementioning
confidence: 99%